1992
DOI: 10.1007/bf00175143
|View full text |Cite
|
Sign up to set email alerts
|

Cortical perfusion response to an electrical stimulation of the auditory nerve in profoundly deaf patients: study with technetium-99m hexamethylpropylene amine oxime single photon emission tomography

Abstract: Brain activation procedures associated with single photon emission tomography (SPET) have recently been developed in healthy controls and diseased patients in order to help in their diagnosis and treatment. We investigated the effects of a promontory test (PT) on the cerebral distribution of technetium-99m hexamethylpropylene amine oxime (99mTc-HMPAO) in 7 profoundly deaf patients, 6 PT+ and one PT-. The count variation in the temporal lobe was calculated on 6 coronal slices using the ratio (Rstimulation-Rdepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…An auditory sensation of the stimulus is believed to demonstrate the responsiveness of auditory neurons (House and Brackmann, 1974) and hence to predict the probable success of the planned implantation. However, the exact nature of the correlation between the promontory test result and the underlying neuronal competence is unknown (Smith and Simmons, 1983), and the signiWcance of a negative test is controversial (Luxford, 1989;Scao et al, 1993;Schmidt et al, 2003). Many centers have limited their use of this test to subjects with severe ossiWcating labyrinthitis, or a history of trauma or retrocochlear surgery (Gantz et al, 1993).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…An auditory sensation of the stimulus is believed to demonstrate the responsiveness of auditory neurons (House and Brackmann, 1974) and hence to predict the probable success of the planned implantation. However, the exact nature of the correlation between the promontory test result and the underlying neuronal competence is unknown (Smith and Simmons, 1983), and the signiWcance of a negative test is controversial (Luxford, 1989;Scao et al, 1993;Schmidt et al, 2003). Many centers have limited their use of this test to subjects with severe ossiWcating labyrinthitis, or a history of trauma or retrocochlear surgery (Gantz et al, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…In a recent study, we demonstrated that right temporal activation (posterior and anterior) is correlated with the ability temporally to parse transmitted phonemes in cochlear implant users relying primarily on temporal cues (Mortensen et al, submitted). However, to identify pre-operative predictors of postoperative results, it is potentially important to combine electrical evaluation of the auditory system with functional neuroimaging (Scao et al, 1993;Truy, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A rather uniform bilateral activation of the temporal cortex after pure tones and electrical stimuli, was reported by Le Scao et al (7)(8)(9). On the contrary, PET investigations and previous personal studies with SPET, proved an asymmetrical cortical stimulation, with a statistically significant higher increase in contralateral regions (2)(3)(4)6).…”
Section: T a B mentioning
confidence: 82%
“…Various authors have supported the reliability and usefulness of single photon emission tomography (SPET) in investigating auditory cortex activation in normal and hearing-impaired subjects [2,3,6,15,16,21]. In this paper the features of ABI-induced activation of the auditory cortex were studied by means of SPET.…”
Section: Introductionmentioning
confidence: 99%